Pengaruh intellectual capital terhadap abnormal return saham dan kinerja keuangan (studi pada perusahaan perbankan di bursa efek indonesia tahun 2011-2015) - Nanda Entika Paradesia; Zainal Ilmi; Maryam Nadir (KINERJA, 2016)
The purpose of this study was to examine the effect of intellectual capital to abnormal stock return and financial perfomance of banking firms. The abnormal stock return was measured by cumulative abnormal return (CAR), and average abnormal return (AAR), the companys financial perfomance measured by return on assets (ROA), assets turn over (ATO) and growth in revenue (GR). Laten variables used in this study was the perfomance of intellectual capital as measured by VAIC (VACA, VAHU, STVA). The sample study was using banking company listed in Indonesia Stock Exchange (IDX) for 2011-2015. Research data using purposive sampling method. Data obtained amounted to 75 companies in the period 2011-2015. This study uses PLS version 3.0 to analyze the data. The result showed that significant intellectual capital positive significantly effect the abnormal stock return and financial perfomance that measured by CAR, AAR, ROA and ATO, but no effect on GR. Overall, this research found that structural capital (STVA) gives the most contribution in creating value added of the company.Keywords: intellectual capital, cumulative abnormal return (CAR), and average abnormal return (AAR), return on assets (ROA), assets turn over (ATO), growth in revenue (GR)